Evaluación y desarrollo de competencias socioemocionales a través de la música en estudiantes universitarios = Abweichender Titel: Assessment and Development of Social-Emotional Skills through Music in University Students - Moral-Marcos, María Teresa del (Cauriensia, 2025)
Higher education plays a critical role in the development of socio-emotional competencies, which are essential for students' social inclusion, academic performance, and professional development. The aim of this study was to examine university students' perceptions of their socio-emotional competencies using the Social-Emotional Competence Scale (ECSE). Data were collected on personal variables, such as age, and academic variables, including field of study. The analyses revealed a weak but positive correlation between age and overall socio-emotional competencies. In addition, statistically significant differences were observed between students from Science and Social Science disciplines, as well as across age groups, with moderate effect sizes. The findings also suggest that students’ self-perceptions may not fully align with standardised ECSE scores, underscoring the importance of combining both qualitative and quantitative assessment approaches. Furthermore, the results support the incorporation of active learning methodologies and the use of artistic languages, including music, visual arts, and theatre, to facilitate the development of socio-emotional skills. The study highlights the need for student-centred teaching strategies and comprehensive evaluation frameworks to enhance socio-emotional learning and the quality of higher education, providing empirical evidence to inform educational innovation.